Factors Influencing Post-traumatic Stress Symptoms in Chinese Adolescents During the COVID-19 Pandemic - Ke, Siyuan; Sun, Li; Zhou, Jiawei; Wang, Yini; Bu, Tianyi; Chu, Haiyun; Yang, Jiarun; Wang, Wenbo; Wang, Wantong; Li, Jiarui; Zhao, Lu; Qiao, Zhengxue; et al. (Frontiers in Psychiatry, 2022)
In order to investigate the prevalence of post-traumatic stress symptoms （PTSS） and analyze the influencing factors of PTSS among adolescents in a large sample study during the COVID-19 pandemic, we did a cross-sectional study by collected demographic data and mental health measurements from a large group of 175,318 adolescents in 32 Chinese provinces and autonomous regions, using the Impact of Event Scale-Revised (IES-R) was used to measure the PTSS of the participants. The results showed that the prevalence of PTSS was 35.7% in Chinese adolescents during the COVID-19 pandemic. Binary logistic regression analysis showed that, for the personal risk factors, the older age, female gender, the personality domains of extroversion, the irregular sleep schedule, lacking of aerobic exercise and lacking of peer support, were associated with the higher levels of PTSS. The family subjective and objective factors were associated with higher levels of PTSS. Our findings suggested that family factors are the most important factors affecting Chinese adolescents' PTSS due to the longtime of home quarantine.